Поліпшення форми вхідних струмів матричних перетворювачів в умовах несиметричної та/або несинусоїдальної системи напруг мережі живлення - Михальський, В.М.; Соболєв, В.М.; Чопик, В.В.; Шаповал, І.А. (Технічна електродинаміка, 2015)
Розроблено і досліджено способи керування матричним перетворювачем (МП) на загальній базі алгоритму регулювання вхідної реактивної потужності МП, які спрямовані на поліпшення якості вхідних струмів МП в умовах несиметричної і/або несинусоїдальної системи напруг мережі живлення. З цією метою розглянуто різні варіанти завдання напрямку просторового вектора вхідного струму по відношенню до просторового вектора вхідної напруги за рахунок належного регулювання реактивної складової струму. Моделювання показало дієвість запропонованого підходу щодо поліпшення форми вхідних струмів МП з урахуванням реальних умов комутацій і дискретного формування цих струмів. Разработаны и исследованы способы управления матричным преобразователем (МП) на общей базе алгоритма регулирования входной реактивной мощности МП, направленные на улучшение качества входных токов МП в условиях несимметричной и/или несинусоидальной системы напряжений сети. С этой целью рассмотрены различные варианты задания направления пространственного вектора входного тока по отношению к пространственному вектору входного напряжения за счет надлежащего регулирования реактивной составляющей тока. Моделирование показало достоверность и действенность предложенного подхода по улучшению формы входных токов МП с учетом реальных условий коммутаций и дискретного формирования этих токов. The paper aims to study methods of the matrix converter (MC) control on the base of input reactive power control algorithm for improving the quality of MC input current under unbalanced and/or nonsinusoidal input voltage conditions. Simple assurance of the uniformity of the power consumed by the load in these conditions leads to an additional modulation of the active component of the input current and thereby a distortion of its waveform. A dynamic modulation of its reactive component that does not affect the load is possible in order to correct and improve the quality of current consumed from the network. Different versions of setting of the direction of the current space vector with respect to the input voltage space vector have been generalized. The initial condition is the information about the instantaneous values of the MC input voltage space vector, the space vector of the fundamental harmonic of positive sequence and MC output current space vector. It is shown how the relationship between modulation of the direction of the input current space vector and immediate reference and realization of its reactive component is set. Analytical expressions of reference of the transfer ratio of the active component of the output current to the reactive component of the input current and the algorithm of the implementation have been summarized. The simulation showed the reliability and effectiveness of the proposed approach to improve the waveform of the MC input currents based on actual conditions and switching discrete formation of these currents.